2005
DOI: 10.1007/s00468-005-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Stem and leaf water potentials, gas exchange, sap flow, and trunk diameter fluctuations for detecting water stress in lemon trees

Abstract: The sensitivity of continuous (on a whole-day basis) and discretely (at midday) measured indicators of the plant water status in adult lemon trees in response to a cycle of water deprivation and recovery, and the feasibility of obtaining baselines for tree water status indicators was investigated in 30-year-old Fino lemon trees (Citrus limon (L.) Burm. fil.) grafted on sour orange (C. aurantium L.) rootstocks. Control plants (T0) were irrigated daily above their crop water requirements in order to obtain non-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
0
20

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 34 publications
(40 reference statements)
10
51
0
20
Order By: Relevance
“…On small timescales (hourly to daily), incremental stem growth (and shrinkage) is measured using precision dendrometers that contain linear-variable-displacement transducers (Zweifel et al, 2005;Drew et al, 2008;Drew and Downes, 2009). Changes in maximum daily trunk shrinkage arising from reduced water availability occur earlier and stronger than changes in stomatal conductance, stem water potential or transpiration (Ortuno et al, 2006;Conejero et al, 2007Conejero et al, , 2011Galindo et al, 2013). Nonetheless, rates of sap flow declined with maximum daily stem shrinkage, both of which responded exponentially to changes in depth-to-groundwater (Ma et al, 2013).…”
Section: Effects Of Groundwater On Growth and Dendrochronological Traitsmentioning
confidence: 99%
“…On small timescales (hourly to daily), incremental stem growth (and shrinkage) is measured using precision dendrometers that contain linear-variable-displacement transducers (Zweifel et al, 2005;Drew et al, 2008;Drew and Downes, 2009). Changes in maximum daily trunk shrinkage arising from reduced water availability occur earlier and stronger than changes in stomatal conductance, stem water potential or transpiration (Ortuno et al, 2006;Conejero et al, 2007Conejero et al, , 2011Galindo et al, 2013). Nonetheless, rates of sap flow declined with maximum daily stem shrinkage, both of which responded exponentially to changes in depth-to-groundwater (Ma et al, 2013).…”
Section: Effects Of Groundwater On Growth and Dendrochronological Traitsmentioning
confidence: 99%
“…In deciduous fruit (Cohen et al 2001;Marsal et al 2002;Intrigliolo and Castel 2006b) and citrus (Ortuño et al 2006) tree species, MDS and TGR were found to be responsive to changes in moisture availability. In all these cases plant water deWcit increased trunk shrinkage and decreased trunk growth.…”
Section: Introductionmentioning
confidence: 99%
“…Sap flow-related measurements are widely used in research for in situ determinations of plant water consumption and transpiration dynamics (Figure 7), and their potential for irrigation scheduling has been assessed by Nadezhdina [93], Fernández et al [94,95] and Jones [30], among others. Devices to schedule irrigation automatically from sap flow measurements have been designed and tested in fruit tree orchards [96,97], and comparisons with other methods to monitor plant water stress and to schedule irrigation have been made for a variety of crops, including apple [93], grapes [98], lemon [99], plum [100] and olive [101,102], among other species. In a recent review, Fernández [20] analysed the applicability of sap flow-related measurements for assessing water stress and irrigation scheduling in commercial orchards.…”
Section: Sap Flowmentioning
confidence: 99%